Promoting school climate and health outcomes with the SEHER multi-component secondary school intervention in Bihar, India: a cluster-randomised controlled trial. Issue 10163 (8th December 2018) - Shinde, Sachin; Weiss, Helen A; Varghese, Beena; Khandeparkar, Prachi; Pereira, Bernadette; Sharma, Amit; Gupta, Rajesh; Ross, David A; Patton, George; Patel, Vikram
Summary: Background: School environments affect health and academic outcomes. With increasing secondary school retention in low-income and middle-income countries, promoting quality school social environments could offer a scalable opportunity to improve adolescent health and wellbeing. Methods: We did a cluster-randomised trial to assess the effectiveness of a multi-component whole-school health promotion intervention (SEHER) with integrated economic and process evaluations in grade 9 students (aged 13–14 years) at government-run secondary schools in the Nalanda district of Bihar state, India. Schools were randomly assigned (1:1:1) to three groups: the SEHER intervention delivered by a lay counsellor (the SEHER Mitra [SM] group), the SEHER intervention delivered by a teacher (teacher as SEHER Mitra [TSM] group), and a control group in which only the standard government-run classroom-based life-skills Adolescence Education Program was implemented. The primary outcome was school climate measured with the Beyond Blue School Climate Questionnaire (BBSCQ). Students were assessed at the start of the academic year (June, 2015) and again 8 months later at the end of the academic year (March, 2016) via self-completed questionnaires. This study is registered with ClinicalTrials.gov, number NCT02484014 . Findings: Of the 112 eligible schools in the Nalanda district, 75 were randomly selected to participate in the trial. We randomly assigned 25 schools to each of the three groups. One school subsequently dropped out of the TSM group, leaving 24 schools in this group. The baseline survey included a total of 13 035 participants, and the endpoint survey included 14 414 participants. Participants in the SM-delivered intervention schools had substantially higher school climate scores at endpoint survey than those in the control group (BBSCQ baseline-adjusted mean difference [aMD] 7·57 [95% CI 6·11–9·03]; effect size 1·88 [95% CI 1·44–2·32], p<0·0001) and the TSM-delivered intervention (aMD 7·57 [95% CI 6·06–9·08]; effect size 1·88 [95% CI 1·43–2·34], p<0·0001). There was no effect of the TSM-delivered intervention compared with control (aMD −0·009 [95% CI −1·53 to 1·51], effect size 0·00 [95% CI −0·45 to 0·44], p=0·99). Compared with the control group, participants in the SM-delivered intervention schools had moderate to large improvements in the secondary outcomes of depression (aMD −1·23 [95% CI −1·89 to −0·57]), bullying (aMD −0·91 [95% CI −1·15 to −0·66]), violence victimisation (odds ratio [OR] 0·62 [95% CI 0·46–0·84]), violence perpetration (OR 0·68 [95% CI 0·48–0·96]), attitude towards gender equity (aMD 0·41 [95% CI 0·21–0·61]), and knowledge of reproductive and sexual health (aMD 0·29 [95% CI 0·06–0·53]). Similar results for these secondary outcomes were noted for the comparison between SM-delivered intervention schools and TSM-delivered intervention schools (depression: aMD −1·23 [95% CI −1·91 to −0·55]; bullying: aMD −0·83 [95% CI −1·08 to −0·57]; violence victimisation: OR 0·49 [95% CI 0·35–0·67]; violence perpetration: OR 0·49 [95% CI 0·34–0·71]; attitude towards gender equity: aMD 0·23 [95% CI 0·02–0·44]; and knowledge of reproductive and sexual health: aMD 0·22 [95% CI −0·02 to 0·47]). However, no effects on these secondary outcomes were observed for the TSM-delivered intervention schools compared with the control group (depression: aMD −0·03 [95% CI −0·70 to 0·65]; bullying: aMD −0·08 [95% CI −0·34 to 0·18]; violence victimisation: OR 1·27 [95% CI 0·93–1·73]; violence perpetration: OR 1·37 [95% CI 0·95–1·95]; attitude towards gender equity: aMD 0·17 [95% CI −0·09 to 0·38]; and knowledge of reproductive and sexual health: aMD 0·06 [95% CI −0·18 to 0·32]). Interpretation: The multi-component whole-school SEHER health promotion intervention had substantial beneficial effects on school climate and health-related outcomes when delivered by lay counsellors, but no effects when delivered by teachers. Future research should focus on the evaluation of the scaling up of the SEHER intervention in diverse contexts and delivery agents. Funding: John D. and Catherine T. MacArthur Foundation, USA and the United Nations Population Fund India Office.